2022
DOI: 10.14744/felt.2022.4.1.6
|View full text |Cite
|
Sign up to set email alerts
|

EFL Teachers’ Opinions on the Use of L1 in L2 Classrooms: Role of Experience and Context

Abstract: The use of native language (L1) in foreign language classrooms (L2) has been studied from various perspectives, and it is important to investigate teachers' opinions about the use of L1 to better understand their practice. This study investigates the role of experience on the attitudes of language teachers towards the use of L1 in L2 classes. The participants of this research were pre-service and in-service teachers, and research questions aimed to reveal the language teaching areas that they agreed and/or dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The results of this study were comparable to those of Kıcır and Mahmutoğlu's (2013) and Sarandi's (2013) studies in that a certain level of L1 usage was deemed acceptable. Taner and Balıkçı, (2022) explained the shift from negative to positive attitude towards the use of L1 in terms of experience and context. The results of their study indicated that both experience and the L2 teaching and learning context were influential on teachers' practices and beliefs while experienced teachers were more tolerant of the use of L1 in all of their practices than pre-service teachers, who tended to favour English only.…”
Section: Teachers' Opinion Towards the Use Of L1mentioning
confidence: 99%
“…The results of this study were comparable to those of Kıcır and Mahmutoğlu's (2013) and Sarandi's (2013) studies in that a certain level of L1 usage was deemed acceptable. Taner and Balıkçı, (2022) explained the shift from negative to positive attitude towards the use of L1 in terms of experience and context. The results of their study indicated that both experience and the L2 teaching and learning context were influential on teachers' practices and beliefs while experienced teachers were more tolerant of the use of L1 in all of their practices than pre-service teachers, who tended to favour English only.…”
Section: Teachers' Opinion Towards the Use Of L1mentioning
confidence: 99%
“…In recent decades, there has been a growing body of literature re-evaluating the use of the first language (L1) in the context of second and foreign language teaching and learning (Cook, 2001;de la Campa & Nassaji, 2009;Edstrom, 2006;Littlewood & Yu, 2011;Macaro, 2001;Storch & Wigglesworth, 2003;Saruwatashi, 2020;Hanif, 2020;Algazo, 2022;Taner & Balıkçı, 2022). These researchers have explored the potential benefits of judicious L1 use, challenging the traditional view that strictly restricts L1 in the language learning process.…”
Section: Introductionmentioning
confidence: 99%